Sequence Determinants of Intracellular Phase Separation by Complex Coacervation of a Disordered Protein - Pak, Chi W.; Kosno, Martyna; Holehouse, Alex S.; Padrick, Shae B.; Mittal, Anuradha; Ali, Rustam; Yunus, Ali A.; Liu, David R.; Pappu, Rohit V.; Rosen, Michael K. (Molecular cell, 2016)
Liquid-liquid phase separation, driven by collective interactions among multivalent and intrinsically disordered proteins, is thought to mediate the formation of membrane-less organelles in cells. Using parallel cellular and in vitro assays, we show that the Nephrin intracellular domain (NICD), a disordered protein, drives intracellular phase separation via complex coacervation, whereby the negatively charged NICD co-assembles with positively charged partners to form protein-rich dense liquid droplets. Mutagenesis reveals that the driving force for phase separation depends on the overall amino acid composition and not the precise sequence of NICD. Instead, phase separation is promoted by one or more regions of high negative charge density and aromatic/hydrophobic residues that are distributed across the protein. Many disordered proteins share similar sequence characteristics with NICD, suggesting that complex coacervation may be a widely used mechanism to promote intracellular phase separation. [Display omitted] •Disordered Nephrin intracellular domain (NICD) forms phase-separated nuclear bodies•NICD phase separates via complex coacervation•Aromatic/hydrophobic residues and high (−) charge density promote phase separation•Disordered regions with NICD-like sequence features are common in human proteome Pak et al. describe cellular liquid-liquid phase separation of a negatively charged intrinsically disordered protein, the Nephrin intracellular domain. Phase separation is driven by co-assembly with positively charged partners, a process termed complex coacervation. Disordered regions with NICD-like sequence features are common in the human proteome, suggesting complex coacervation may be widespread.